2010
DOI: 10.1177/0891243209355978
|View full text |Cite
|
Sign up to set email alerts
|

Gender Work in a Feminized Profession

Abstract: Veterinary medicine has undergone dramatic, rapid feminization while in many ways remaining gendered masculine. With women constituting approximately half of its practitioners and nearly 80 percent of students, veterinary medicine is the most feminized of the comparable health professions. Nevertheless, the culture of veterinary medicine glorifies stereotypically masculine actions and attitudes. This article examines how women veterinarians understand the gender dynamics within the profession. Our analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(46 citation statements)
references
References 37 publications
1
32
0
2
Order By: Relevance
“…By classifying certain female spectators as inauthentic simply by their dress, their conversations, or their presumed lack of knowledge of sport further marginalises a population of sport spectators that we are striving to understand. This supports the notion that in attempting to fit into hegemonic masculine definitions of a culture some women take on certain elements of hegemonic masculinity to shape their position within that culture (see also Irvine & Vermilya, 2010;Messerschmidt, 2012). This situation may be particularly salient for us as we negotiate our own sport fandom in that we may inadvertently adopt the same behaviours that men have used to subordinate women in the sport fan definition (Jones, 2008).…”
Section: Marginalisation Of Other Womensupporting
confidence: 64%
See 1 more Smart Citation
“…By classifying certain female spectators as inauthentic simply by their dress, their conversations, or their presumed lack of knowledge of sport further marginalises a population of sport spectators that we are striving to understand. This supports the notion that in attempting to fit into hegemonic masculine definitions of a culture some women take on certain elements of hegemonic masculinity to shape their position within that culture (see also Irvine & Vermilya, 2010;Messerschmidt, 2012). This situation may be particularly salient for us as we negotiate our own sport fandom in that we may inadvertently adopt the same behaviours that men have used to subordinate women in the sport fan definition (Jones, 2008).…”
Section: Marginalisation Of Other Womensupporting
confidence: 64%
“…As noted by Connell and Messerschmidt (2005, p. 844), ''To sustain a given pattern of hegemony requires the policing of men as well as the exclusion or discrediting of women.'' The reformulation of the concept of hegemonic masculinity draws attention to the situation of women appropriating some elements of hegemonic masculinity to shape their careers (see also Irvine & Vermilya, 2010;Messerschmidt, 2012). This may be particularly salient for women managing their roles as sport fans in that they may adopt behaviours that men have used to keep women out of the sport fan context (Jones, 2008).…”
Section: Hegemonic Masculinitymentioning
confidence: 96%
“…Multiple studies have found that women often ignore, or altogether dismiss, sexism at work in some work contexts (Bird & Rhoton, 2011;Britton, 2017;Harris & Giuffre, 2015;Irvine & Vermilya, 2010;Rhoton, 2011). Britton's (2017) study of women faculty identified a paradox: Despite their recognition of gender inequalities and biases, women said that gender does not matter at work and downplay its ubiquity.…”
Section: Lack Of Recognition Of Gender Inequality At Workmentioning
confidence: 99%
“…In their study of the culinary industry, Harris and Giuffre (2015) found that women chefs similarly maintained that gender did not matter in their work and espoused a meritocracy rhetoric despite clear evidence that gender inequality was structured into professional kitchens (for another study of women supporting a meritocratic vision of their work, see Seron, Silbey, Cech, & Rubineau, 2018). Likewise, Irvine and Vermilya (2010) analyzed a newly feminized occupation, veterinary medicine. Women veterinarians claimed that women who received lower pay than men did not negotiate enough for a higher salary.…”
Section: Lack Of Recognition Of Gender Inequality At Workmentioning
confidence: 99%
“…However, when person stereotypes cross with job stereotypes, gendered prescriptions for the person often triumph. For example, male nurses are expected to show (masculine) leadership abilities (e.g., Evans, 1997), while female executives and veterinarians should demonstrate (feminine) caring attributes (Irvine & Vermilya, 2010;Rudman & Glick, 2001). The tenacity of person-based gender stereotyping has also been clear in court cases.…”
Section: The Role Of Gender Stereotypingmentioning
confidence: 99%